2016
DOI: 10.1088/1475-7516/2016/10/042
|View full text |Cite
|
Sign up to set email alerts
|

New CMB constraints for Abelian Higgs cosmic strings

Abstract: Abstract. We present cosmic microwave background (CMB) power spectra from recent numerical simulations of cosmic strings in the Abelian Higgs model and compare them to CMB power spectra measured by Planck. We obtain revised constraints on the cosmic string tension parameter Gµ. For example, in the ΛCDM model with the addition of strings and no primordial tensor perturbations, we find Gµ < 2.0×10 −7 at 95% confidence, about 20% lower than the value obtained from previous simulations, which had 1/64 of the spati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 39 publications
1
113
0
Order By: Relevance
“…Stronger constraints can be derived from bounds on high-energy particle emission [52], or Cosmic Microwave Background fluctuations [3] if the fields making the string are decoupled from the Standard Model.…”
Section: E Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stronger constraints can be derived from bounds on high-energy particle emission [52], or Cosmic Microwave Background fluctuations [3] if the fields making the string are decoupled from the Standard Model.…”
Section: E Conclusionmentioning
confidence: 99%
“…Field theory simulations have successfully been used for many years to calculate the power spectrum of Cosmic Microwave Background (CMB) fluctuations from cosmic strings [1][2][3]. Searching for the imprint of strings is a powerful way to search for phase transitions just below the energy scale of inflation, which could be as high as the Grand Unification scale.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of cosmic strings can be tested using the cosmic microwave background (CMB) measurements. Confronting experimental CMB data with numerical simulations of cosmic string networks [20][21][22][23], the string tension is constrained to be smaller than a few 10 −7 .…”
Section: Introductionmentioning
confidence: 99%
“…For an actual Nambu-Goto string simulation, Lazanu & Shellard (2015) has computed a limit of Gµ < 1.5 × 10 −7 . And for Abelian-Higgs strings Lizarraga et al (2016) have found the limit to be 2.0 × 10 −7 .…”
Section: Cosmological Detection Of Cosmic Stringsmentioning
confidence: 99%